Flame-retardant light alloy for aviation and preparation process thereof

Through alloying of components such as rhenium, rare earth elements and calcium and porous neodymium hydroxide nanosheet refining agent, the flammability problem of magnesium alloy is solved, and a high-strength lightweight flame-retardant magnesium alloy is prepared, which improves the flame retardant and mechanical properties of magnesium alloys.

CN120082780APending Publication Date: 2025-06-03JIANGSU ZHONGFU ALUMINUM MAGNESIUM TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510150675.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-11
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

Magnesium alloys are prone to oxidation and combustion, resulting in difficulty in production and processing, limiting their wide application.

Method used

The alloying of components such as rhenium, rare earth elements and calcium is adopted to improve the mechanical properties through solid solution strengthening and second phase precipitation, and porous neodymium hydroxide nanosheets are used as refining agents to improve the flame retardant performance and the stability of the oxide film.

Benefits of technology

Prepare a high-strength lightweight flame-retardant magnesium alloy to reduce the risk of oxidation and combustion, and improve the flame-retardant and mechanical properties of the alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005267988030000081
    Figure BDA0005267988030000081
Patent Text Reader

Abstract

The invention discloses a flame-retardant light alloy for aviation, which comprises the following raw materials in percentage by weight: 8 to 10 percent of aluminum, 0.5 to 1.5 percent of rhenium, 0.5 to 1.5 percent of zinc, 0.02 to 0.05 percent of manganese, 0.001 to 0.005 percent of beryllium, 0.1 to 0.2 percent of strontium, 0.6 to 1.2 percent of calcium, 0.5 to 1.5 percent of tin and the balance of magnesium and inevitable impurities. Magnesium is added into the smelting furnace, the remaining metal elements are added after magnesium is completely melted, the temperature continues to rise to 700-720 DEG C, a refining agent is added for refining for 10-15 min, then heat preservation and standing are carried out for 10-20 min, slagging-off is carried out, and the flame-retardant light alloy is prepared. Added rhenium improves the mechanical property of the magnesium alloy through solid solution strengthening and second phase precipitation strengthening, meanwhile, the rare earth element can improve the stability of an oxidation film on the surface of the magnesium alloy, and the flame retardant property of the alloy is improved; calcium has good grain refinement and anti-oxidation effects in the magnesium alloy.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of light alloys, and particularly relates to a flame-retardant light alloy for aviation and a preparation process thereof. Background Art

[0002] In the prior art, magnesium alloy is the lightest metal structural material in practical applications. It has the advantages of low specific gravity, high specific strength and specific stiffness, good damping performance, cutting performance and casting performance. Magnesium alloy is highly flammable. Due to the relatively active magnesium metal, magnesium alloy is extremely prone to oxidation and combustion during melting and processing. Therefore, the melting of magnesium alloy is generally carried out in a flame-retardant solvent or a protective atmosphere. This characteristic of magnesium alloy being prone to oxidation and combustion brings great difficulties to the production, processing and treatment of the alloy, and greatly hinders the wide application of magnesium alloy. Therefore, how to obtain an ideal flame-retardant and tough magnesium alloy has always been an important topic in the research field of magnesium alloy. Summary of the Invention

[0003] In order to solve the above technical problems, the present invention provides a flame-retardant light alloy for aviation and a preparation process thereof.

[0004] The object of the present invention can be achieved by the following technical solutions:

[0005] A flame-retardant light alloy for aviation, comprising the following raw materials in weight percentages: 8-10% aluminum, 0.5-1.5% rhenium, 0.5-1.5% zinc, 0.02-0.05% manganese, 0.001-0.005% beryllium, 0.1-0.2% strontium, 0.6-1.2% calcium, 0.5-1.5% tin, and the balance being magnesium and inevitable impurities;

[0006] Rhenium improves the mechanical properties of magnesium alloy through solid solution strengthening and second-phase precipitation strengthening. At the same time, rare earth elements can improve the stability of the surface oxide film of magnesium alloy and enhance the flame-retardant performance of the alloy; calcium has good grain refinement and antioxidant effects in magnesium alloy.

[0007] The flame-retardant light alloy is made through the following steps:

[0008] Add magnesium into a melting furnace, and at the same time add a covering agent. After the magnesium is melted, add the remaining metal elements, heat to melting, continue to raise the temperature to 700-720 °C, add a refining agent and refine for 10-15 minutes, then keep warm and stand for 10-20 minutes, and skim the slag to obtain the flame-retardant light alloy.

[0009] Further, the dosage of the covering agent is 0.8-1.5% of the weight of magnesium.

[0010] Further, the covering agent is composed of potassium chloride, magnesium chloride and sodium chloride mixed in a weight ratio of 1:1:1.

[0011] Further, the refining agent is prepared through the following steps:

[0012] Step S1: Add neodymium nitrate hexahydrate and ammonium nitrate into deionized water, and stir evenly for 15 min to obtain solution a.

[0013] Step S2: Use FTO as the substrate, ultrasonically clean the conductive glass FTO three times with absolute ethanol and acetone respectively, and set aside. Place solution a in an electrolytic cell, use a graphite electrode as the counter electrode, the cleaned FTO as the working electrode, and an Ag / AgCl saturated electrode as the reference electrode. Electro-deposit for 2 h under the conditions of a temperature of 75 °C and a current intensity of 5 mA to obtain porous neodymium hydroxide nanosheets.

[0014] Step S3: Mix the obtained porous neodymium hydroxide nanosheets, magnesium chloride, and potassium chloride evenly according to a weight ratio of 1:1:1 to obtain the refining agent.

[0015] The porous neodymium hydroxide nanosheets are prepared by electro-deposition. The method is simple and easy to implement, has a high repeatability, and has little impact on the environment. The prepared neodymium hydroxide nanosheets have a porous structure and a large specific surface area, so that they have excellent adsorption performance. After being added to the alloy liquid, the special porous flake structure can fill the voids of magnesium oxide, increase the density of the surface layer, reduce the oxidation of the magnesium liquid, and also reduce the oxides in the magnesium liquid, improving the refining effect. Moreover, through its own porous structure and a super-large specific surface area, it can improve the adsorption and combination speed with impurities such as magnesium oxide, playing a role in efficient refining.

[0016] Further, in step S1, control the dosage ratio of neodymium nitrate hexahydrate, ammonium nitrate, and deionized water to be 4.22 - 4.32 g: 5.56 - 5.68 g: 500 mL.

[0017] A preparation process of a flame-retardant light alloy for aviation includes the following steps:

[0018] Add magnesium into a melting furnace, and at the same time add a covering agent. After the magnesium is melted, add the remaining metal elements, heat to melting, continue to heat up to 700 - 720 °C, add the refining agent and refine for 10 - 15 min, then keep warm and stand for 10 - 20 min, and skim the slag to obtain the flame-retardant light alloy.

[0019] The beneficial effects of the present invention:

[0020] The present invention prepares a flame-retardant light alloy for aviation. Using magnesium as the matrix element can achieve the goal of lightweight and high strength. Moreover, the added rhenium improves the mechanical properties of the magnesium alloy through solid solution strengthening and second-phase precipitation strengthening. At the same time, rare earth elements can improve the stability of the surface oxide film of the magnesium alloy and improve the flame-retardant performance of the alloy; calcium has good grain refinement and antioxidant effects in the magnesium alloy.

[0021] The present invention also prepares a refining agent. Porous neodymium hydroxide nanosheets are prepared by an electrodeposition method. The method is simple and easy to implement, has a high repeatability, and has little impact on the environment. The prepared neodymium hydroxide nanosheets have a porous structure and a large specific surface area, thereby having excellent adsorption properties. After being added to the alloy liquid, the special porous flake structure can fill the voids of magnesium oxide, increase the density of the surface layer, reduce the oxidation of the magnesium liquid, and also reduce the oxides in the magnesium liquid, improving the refining effect. Moreover, due to its own porous structure and extremely large specific surface area, it can increase the adsorption and combination speed with impurities such as magnesium oxide, playing a role in efficient refining. Specific Embodiments

[0022] The technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts belong to the scope of protection of the present invention.

[0023] Example 1

[0024] A flame-retardant light alloy for aviation comprises the following raw materials by weight percentage: 8% aluminum, 0.5% rhenium, 0.5% zinc, 0.02% manganese, 0.001% beryllium, 0.1% strontium, 0.6% calcium, 0.5% tin, and the balance is magnesium and inevitable impurities;

[0025] Rhenium improves the mechanical properties of the magnesium alloy through solid solution strengthening and second-phase precipitation strengthening. At the same time, rare earth elements can improve the stability of the surface oxide film of the magnesium alloy and enhance the flame-retardant performance of the alloy; calcium has good grain refinement and antioxidant effects in the magnesium alloy.

[0026] The flame-retardant light alloy is made through the following steps:

[0027] Magnesium is added to a melting furnace, and a covering agent is added at the same time. After the magnesium is melted, the remaining metal elements are added, heated to melting, and further heated to 700 °C, then refined with a refining agent for 10 min, and then kept warm and static for 10 min, and the slag is skimmed off to obtain the flame-retardant light alloy.

[0028] The dosage of the covering agent is 0.8% of the weight of magnesium.

[0029] The covering agent is composed of potassium chloride, magnesium chloride, and sodium chloride in a weight ratio of 1:1:1.

[0030] The refining agent is made through the following steps:

[0031] Step S1: Add neodymium nitrate hexahydrate and ammonium nitrate into deionized water, and stir evenly for 15 min to obtain solution a. Control the dosage ratio of neodymium nitrate hexahydrate, ammonium nitrate and deionized water to be 4.22 g: 5.56 g: 500 mL;

[0032] Step S2: Use FTO as the substrate. Ultrasonically clean the conductive glass FTO three times with anhydrous ethanol and acetone respectively, and set aside. Place solution a in an electrolytic cell. Use a graphite electrode as the counter electrode, the cleaned FTO as the working electrode, and an Ag / AgCl saturated electrode as the reference electrode. Electrodeposit for 2 h at a temperature of 75 °C and a current intensity of 5 mA to obtain porous neodymium hydroxide nanosheets;

[0033] Step S3: Mix the obtained porous neodymium hydroxide nanosheets, magnesium chloride and potassium chloride evenly according to the weight ratio of 1:1:1 to obtain a refining agent.

[0034] Example 2

[0035] A flame-retardant light alloy for aviation, comprising the following raw materials in weight percentage: 8% aluminum, 0.8% rhenium, 0.8% zinc, 0.03% manganese, 0.002% beryllium, 0.1% strontium, 0.8% calcium, 0.8% tin, and the balance is magnesium and inevitable impurities;

[0036] Rhenium improves the mechanical properties of the magnesium alloy through solid solution strengthening and second-phase precipitation strengthening. At the same time, rare earth elements can improve the stability of the surface oxide film of the magnesium alloy and enhance the flame-retardant performance of the alloy; calcium has good grain refinement and antioxidant effects in the magnesium alloy.

[0037] This flame-retardant light alloy is made through the following steps:

[0038] Add magnesium into a melting furnace, and at the same time add a covering agent. After the magnesium is melted, add the remaining metal elements, heat to melting, continue to heat up to 700 °C, add a refining agent and refine for 12 min, then keep warm and stand for 12 min, and skim the slag to obtain the flame-retardant light alloy.

[0039] The dosage of the covering agent is 1% of the weight of magnesium.

[0040] The covering agent is composed of potassium chloride, magnesium chloride and sodium chloride mixed according to the weight ratio of 1:1:1.

[0041] The refining agent is made through the following steps:

[0042] Step S1: Add neodymium nitrate hexahydrate and ammonium nitrate into deionized water, and stir evenly for 15 min to obtain solution a. Control the dosage ratio of neodymium nitrate hexahydrate, ammonium nitrate and deionized water to be 4.25 g: 5.6 g: 500 mL;

[0043] Step S2: Using FTO as the substrate, ultrasonically clean the conductive glass FTO three times with absolute ethanol and acetone respectively, and set aside; Place solution a in an electrolytic cell, use a graphite electrode as the counter electrode, the cleaned FTO as the working electrode, and an Ag / AgCl saturated electrode as the reference electrode, and perform electrodeposition for 2 h at a temperature of 75 °C and a current intensity of 5 mA to obtain porous neodymium hydroxide nanosheets;

[0044] Step S3: Mix the obtained porous neodymium hydroxide nanosheets, magnesium chloride and potassium chloride evenly according to a weight ratio of 1:1:1 to obtain a refining agent.

[0045] Example 3

[0046] A flame-retardant light alloy for aviation, comprising the following raw materials in weight percentages: 9% aluminum, 1.2% rhenium, 1.2% zinc, 0.04% manganese, 0.004% beryllium, 0.18% strontium, 1% calcium, 1.2% tin, and the balance is magnesium and inevitable impurities;

[0047] Rhenium improves the mechanical properties of the magnesium alloy through solid solution strengthening and second-phase precipitation strengthening. At the same time, rare earth elements can improve the stability of the surface oxide film of the magnesium alloy and enhance the flame-retardant performance of the alloy; Calcium has good grain refinement and antioxidant effects in the magnesium alloy.

[0048] This flame-retardant light alloy is made through the following steps:

[0049] Add magnesium into a melting furnace, and at the same time add a covering agent. After the magnesium is melted, add the remaining metal elements, heat to melting, continue to heat up to 700 °C, add the refining agent and refine for 10 min, then keep warm and stand for 15 min, and skim the slag to obtain the flame-retardant light alloy.

[0050] The dosage of the covering agent is 1.2% of the weight of magnesium.

[0051] The covering agent is composed of potassium chloride, magnesium chloride and sodium chloride mixed according to a weight ratio of 1:1:1.

[0052] The refining agent is made through the following steps:

[0053] Step S1: Add neodymium nitrate hexahydrate and ammonium nitrate into deionized water, stir evenly for 15 min to obtain solution a, and control the dosage ratio of neodymium nitrate hexahydrate, ammonium nitrate and deionized water to be 4.30 g: 5.62 g: 500 mL;

[0054] Step S2: Using FTO as the substrate, ultrasonically clean the conductive glass FTO three times with absolute ethanol and acetone respectively, and set aside; Place solution a in an electrolytic cell, use a graphite electrode as the counter electrode, the cleaned FTO as the working electrode, and an Ag / AgCl saturated electrode as the reference electrode, and electro-deposit for 2 h under the conditions of a temperature of 75 °C and a current intensity of 5 mA to obtain porous neodymium hydroxide nanosheets;

[0055] Step S3: Mix the obtained porous neodymium hydroxide nanosheets, magnesium chloride and potassium chloride evenly according to a weight ratio of 1:1:1 to obtain a refining agent.

[0056] Example 4

[0057] A flame-retardant light alloy for aviation, comprising the following raw materials in weight percentages: 10% aluminum, 1.5% rhenium, 1.5% zinc, 0.05% manganese, 0.005% beryllium, 0.2% strontium, 1.2% calcium, 1.5% tin, and the balance is magnesium and inevitable impurities;

[0058] Rhenium improves the mechanical properties of the magnesium alloy through solid solution strengthening and second-phase precipitation strengthening. At the same time, rare earth elements can improve the stability of the surface oxide film of the magnesium alloy and improve the flame-retardant performance of the alloy; Calcium has good grain refinement and antioxidant effects in the magnesium alloy.

[0059] This flame-retardant light alloy is made through the following steps:

[0060] Add magnesium to a melting furnace, and at the same time add a covering agent. After the magnesium is melted, add the remaining metal elements, heat to melting, continue to raise the temperature to 720 °C, add the refining agent and refine for 15 min, then keep warm and stand still for 20 min, and skim the slag to obtain the flame-retardant light alloy.

[0061] The dosage of the covering agent is 1.5% of the weight of magnesium.

[0062] The covering agent is composed of potassium chloride, magnesium chloride and sodium chloride mixed according to a weight ratio of 1:1:1.

[0063] The refining agent is made through the following steps:

[0064] Step S1: Add neodymium nitrate hexahydrate and ammonium nitrate to deionized water, stir evenly at a constant speed for 15 min to obtain solution a, and control the dosage ratio of neodymium nitrate hexahydrate, ammonium nitrate and deionized water to be 4.32 g: 5.68 g: 500 mL;

[0065] Step S2: Use FTO as the substrate. Ultrasonically clean the conductive glass FTO three times with absolute ethanol and acetone respectively, and set aside. Place solution a in an electrolytic cell. Use a graphite electrode as the counter electrode, the cleaned FTO as the working electrode, and an Ag / AgCl saturated electrode as the reference electrode. Electro-deposit for 2 h under the conditions of a temperature of 75 °C and a current intensity of 5 mA to obtain porous neodymium hydroxide nanosheets.

[0066] Step S3: Mix the obtained porous neodymium hydroxide nanosheets, magnesium chloride, and potassium chloride evenly according to a weight ratio of 1:1:1 to obtain a refining agent.

[0067] Comparative Example 1

[0068] This comparative example is a flame-retardant magnesium alloy produced by a certain company on the market.

[0069] Detect the properties of the magnesium alloys prepared in Examples 1 - 4. The results are shown in Table 1 below:

[0070] The mechanical property test was carried out according to the national standard GB6397 - 86 "Metal Tensile Test Specimens" for processing and testing. The test equipment was a (SHI MADZU) AG-I 250 kN precision universal testing machine tensile machine, and the tensile speed was 1 mm / min.

[0071] Table 1

[0072]

[0073] It can be seen from Table 1 above that the magnesium alloys prepared in Examples 1 - 4 of the present invention have good flame-retardant properties and excellent mechanical properties, indicating that the added rhenium improves the mechanical properties of the magnesium alloy through solid solution strengthening and second-phase precipitation strengthening. At the same time, rare earth elements can improve the stability of the surface oxide film of the magnesium alloy and enhance the flame-retardant property of the alloy; calcium has good grain refinement and antioxidant effects in the magnesium alloy.

[0074] The above content is only an example and explanation of the concept of the present invention. Those skilled in the art of this technology can make various modifications or supplements to the described specific embodiments or use similar methods for substitution, as long as they do not deviate from the concept of the invention or exceed the scope defined by this claims, they should all fall within the protection scope of the present invention.

Claims

1. A flame retardant light alloy for aviation, characterized in that: The invention comprises the following raw materials in weight percentage: 8-10% aluminum, 0.5-1.5% rhenium, 0.5-1.5% zinc, 0.02-0.05% manganese, 0.001-0.005% beryllium, 0.1-0.2% strontium, 0.6-1.2% calcium, 0.5-1.5% tin, and the balance is magnesium and unavoidable impurities; The flame retardant light alloy is made by the following steps: Add magnesium into the smelting furnace, add covering agent at the same time, add remaining metal elements after magnesium is completely dissolved, heat until melted, continue to heat to 700-720℃, add refining agent and refine for 10-15min, then keep warm and let stand for 10-20min, skim off the slag, and obtain flame retardant light alloy.

2. The flame retardant light alloy for aviation according to claim 1, characterized in that: The amount of the covering agent used is 0.8-1.5% of the weight of magnesium.

3. The flame retardant light alloy for aviation according to claim 1, characterized in that: The covering agent is a mixture of potassium chloride, magnesium chloride and sodium chloride in a weight ratio of 1:1:

1.

4. The flame retardant light alloy for aviation according to claim 1, characterized in that: The refining agent is prepared by the following steps: Step S1, adding neodymium nitrate hexahydrate and ammonium nitrate into deionized water, stirring at a constant speed for 15 minutes, to prepare solution a; Step S2, using FTO as a substrate, ultrasonically cleaning the conductive glass FTO with anhydrous ethanol and acetone three times respectively, and setting aside; placing solution a in an electrolytic cell, using a graphite electrode as a counter electrode, the cleaned FTO as a working electrode, and an Ag / AgCl saturated electrode as a reference electrode, and electro-depositing for 2 hours at a temperature of 75° C. and a current intensity of 5 mA to obtain porous neodymium hydroxide nanosheets; Step S3: uniformly mix the prepared porous neodymium hydroxide nanosheets, magnesium chloride and potassium chloride in a weight ratio of 1:1:1 to prepare a refining agent.

5. The flame retardant light alloy for aviation according to claim 1, characterized in that: In step S1, the dosage ratio of neodymium nitrate hexahydrate, ammonium nitrate and deionized water is controlled to be 4.22-4.32 g: 5.56-5.68 g: 500 mL.

6. The process for preparing a flame retardant light alloy for aviation according to claim 1, characterized in that: The steps include: Add magnesium into the smelting furnace, add covering agent at the same time, add remaining metal elements after magnesium is completely dissolved, heat until melted, continue to heat to 700-720℃, add refining agent and refine for 10-15min, then keep warm and let stand for 10-20min, skim off the slag, and obtain flame retardant light alloy.